2016
DOI: 10.1186/s12902-016-0135-5
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness in hypertensive and type 2 diabetes patients in Ghana: comparison of the cardio-ankle vascular index and central aortic techniques

Abstract: BackgroundDiabetes and hypertension increase arterial stiffness and cardiovascular events in all societies studied so far; sub-Saharan African studies are sparse. We investigated factors affecting arterial function in Ghanaians with diabetes, hypertension, both or neither.MethodTesting the hypothesis that arterial stiffness would progressively increase from controls to multiply affected patients, 270 participants were stratified into those with diabetes or hypertension only, with both, or without either. Cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
(53 reference statements)
2
9
0
Order By: Relevance
“…While previous reports demonstrated that BMI was positively associated with arterial stiffness [ 5 , 20 , 24 , 25 ], BMI was inversely associated with arterial stiffness in this study, consistent with a previous report in non-T2DM patients [ 26 ]. The exact explanation for the conflicting results is unknown; however, a previous study showed higher baPWV levels in T2DM patients with normal BMI and increased visceral adiposity compared to those with higher BMI and normal visceral adiposity [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…While previous reports demonstrated that BMI was positively associated with arterial stiffness [ 5 , 20 , 24 , 25 ], BMI was inversely associated with arterial stiffness in this study, consistent with a previous report in non-T2DM patients [ 26 ]. The exact explanation for the conflicting results is unknown; however, a previous study showed higher baPWV levels in T2DM patients with normal BMI and increased visceral adiposity compared to those with higher BMI and normal visceral adiposity [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…BMI shows a negative association in children, 54 and in patients with hypertension and in subjects with diabetes in Ghana. 55 Similarly, the waist circumference has a negative relationship in subjects with metabolic syndrome. 26 56 …”
Section: Discussionmentioning
confidence: 99%
“…Diabetes patients in Ghana have abnormalities in arterial function that can be measured using aortic pulse wave velocity (PWVao) or cardio-ankle vascular index (CAVI) [ 7 , 8 ]. Both PWVao and CAVI measure arterial stiffness, with CAVI assessing the stiffness in long range of arterial segment (from the aortic root to the ankle arteries), as opposed to PWVao, which assesses the stiffness in the descending aorta, from the aortic root to the bifurcation.…”
Section: Introductionmentioning
confidence: 99%